If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(2x + 4) = 3x + -4 Reorder the terms: 0.5(4 + 2x) = 3x + -4 (4 * 0.5 + 2x * 0.5) = 3x + -4 (2 + 1x) = 3x + -4 Reorder the terms: 2 + 1x = -4 + 3x Solving 2 + 1x = -4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 1x + -3x = -4 + 3x + -3x Combine like terms: 1x + -3x = -2x 2 + -2x = -4 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + -2x = -4 + 0 2 + -2x = -4 Add '-2' to each side of the equation. 2 + -2 + -2x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + -2x = -4 + -2 -2x = -4 + -2 Combine like terms: -4 + -2 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 4(8-x)=2x+16 | | -63+3y+8=2(5y-3)-7 | | 8n+11=10n-11 | | 2(x-5)=15x-4x | | x+(x*.0975)=4.21 | | .3x+1.4=4.2-.1x | | 4m+4=10m-62 | | -7/10m=-1324/24 | | 4+17n-3=9n+85-47 | | 100/900=85/x | | Y=-2x^3-2x^2+60x | | ax-2cx+4ay-8cy= | | 18-8-2=.5(18-2) | | -27+3*27=27+27 | | -u+106=240 | | c-3=2-3 | | 2-4-3-4=4 | | 267=158-u | | 2d+2=3d-4 | | Y=-1/4-4-5 | | 10-6*-3=2(-3-3) | | 27+9w=12w | | 2d+3=3d-4 | | 10-6x-3=2(-3-3) | | 5.2+1.2n=1.84 | | 10u=54+u | | 2(-2)-3+(-2)+1= | | 2x-20=3x+6 | | 0.5x+x=169 | | -3/7(-40-2) | | Cos(x)=0.018 | | 18=-3/7(x-2) |